Collaboration Variability in Autism Spectrum Disorder - Blancas, Maria; Maffei, Giovanni; Sánchez-Fibla, Martí; Vouloutsi, Vasiliki; Verschure, Paul F. M. J. (Frontiers in Human Neuroscience, 2020)
This paper addresses how impairments in prediction in young adults with autism spectrum disorder (ASD) relate to their behavior during collaboration. To assess it, we developed a task where participants play in collaboration with a synthetic agent to maximize their score. The agent’s behavior changes during the different phases of the game, requiring participants to model the agent’s sensorimotor contingencies to play collaboratively. Our results (n = 30, 15 per group) show differences between autistic and neurotypical individuals in their behavioral adaptation to the other partner. Contrarily, there are no differences in the self-reports of that collaboration.